Incidence of postspinal hypotension during cesarean section - Sharma, N.R. (Journal of Institute of Medicine Nepal, 2007)
A total of 200 cases were evaluated for post-spinal hypotension during caesarean section in TU teaching hospital Maharajgunj. Hypotension was reported in 76 (38%) cases. P value >0.05.The Maximum dose of mephentermin given was 30mg and minimum was 6mg. One patient had Spinal block as high as T1 sensory level. Another patient had severe drop of blood pressure followed by unrecorded blood pressure and pulse which was treated with endotracheal intubation, 100%oxygen and vasopressor (Mephentermine). Severe bradycardia (heart rate<40) was recorded in one patient. She was treated with Atropine 0.6mg IV The rest had the level of block between T6 - T4 sensory. Journal of Institute of Medicine Vol.27(3) 2005